Operations management and data analytics modelling economic crises perspective - Awasthi, Lalit Kumar (Taylor & Francis Group, 2022)
This reference text addresses real operation management problem in the thrust areas like health care sector, energy management sector, and industry 4.0. It discusses recent advances and trends in developing the data driven operation management based methodologies, big data analysis, application of computer in industrial engineering, optimization techniques, development of decision support system for industrial operation, role of multi-criteria-decision-making (MCDM) approach in operation management, fuzzy set theory based operation management modeling and lean six sigma.--Provided by publisher.